(untitled) (Web of Teachers: Inderscience Research, 2025)
The article discusses the expression of the traditions of the status singer in the current educational process, the combination of their teaching methods and national values. In teaching students the culture of status, the ways of combining the teacher-apprentice school, musical thinking, breathing and tone systems with modern educational tools are shown.